THE ANALYSIS OF AFFECTIVE FACTORS ENHANCEMENT ON EFL TEACHING ACTIVITY - Purnawati, Purnawati; Kurniawan, Andri; Shopia, Khilda (FKIP, UNIVERSITAS ISLAM SYEKH-YUSUF TANGERANG, 2022)
Learning English has its own challenge for Junior High school students in Indonesia. One of the ways to cope with the challenges is by enhancing students’ affective factors such as self-confidence, language ego, risk-taking willingness, and connecting with first language culture. However, researches on these types of affective factors are insufficient thus the researchers were interested to conduct research on the topic. The current study was implementing the narrative qualitative method, where EFL teaching activity was observed. It intended to analyze the teachers’ effort to develop EFL students’ affective variables. The EFL class observed the 9th grade of a private junior high school in West Java which was involving one EFL teacher and 29 students. The research shows that teachers did give favor the development of students’ affective variables as many as 32% from the lists observed. However, it is not sufficient, not programmed, and not systematical. The researchers suggest the educators systematically enhance students’ affective factors in the classroom setting. For further research, it is recommended to conduct research related to the effective factors with broader scopes and samples. Keywords: Affective Factors, Affective enhancement, EFL Students, Teacher Effort